Clinical Outcomes of Laser In Situ Keratomileusis (LASIK) Using Microkeratome and Laser Femtosecond Flap in Myopic Patients - Sesy Caesarya; Hikmat Wangsaatmadja; Mayang Rini; Feti Karfiati (Majalah Oftalmologi Indonesia, 2015)
Background: This study aimed to compare postoperative visual acuity and complications between flap LASIK creation using microkeratome and femtosecond laser. Method: This is a retrospective observational study. Data were collected from medical record, patient with microkeratome and femtosecond laser flap creations with best corrected visual acuity 6/6 preoperatively.Uncorrected postoperative visual acuity at 1 day, 1 week and 1 month, also complications were recorded. Result: The microkeratome and femtosecond laser group comprised of 130 and 184 eyes respectively. Visual acuity at 1 day follow up were 99.23% ≥6/12 in microkeratome group and 96.20% ≥6/12 in femtosecond laser group (P=0.19), at 1 week follow up were 99.23% ≥6/12 in microkeratome group and 97.82% ≥6/12 in femtosecond laser group (P=0.36) and 1 month follow up were 99.23% ≥6/12 in microkeratome group and 98.37% ≥6/12 in femtosecond laser group (P=0.60). There were significant differences in intraoperative (P=0.00) and postoperative (P=0.04) complications between two groups. Conclusion: There was no significant difference in visual acuity between LASIK flap creation using microkeratome and femtosecond laser at 1day, 1 week and 1month follow up. There were significant differences in intra and postoperative complications between two groups. Keywords: LASIK, microkeratome, femtosecond laser